Trauma Management: Should it be a part of Medical Curriculum? - Marvi Mahesar; Hira Salman; Neha Khatri; Sarah Zafar; Umaima Dhamrah; Aamir Sabih Hydri (Journal of Bahria University Medical and Dental College)
Trauma management is an approach to assess and treat multiply injured patients. Casualties that present within the first two hours of injury are deaths that can be prevented. Medical professionals need to be trained to appraise and manage these patients during this period. A variety of courses are available, designed entirely to teach medical professionals to treat trauma patients. Many counties have adopted these programs and now they are being taught in over 60 countries worldwide. In developing countries, injuries due to trauma are regrettably neglected, and accounts for more than five million deaths each year. This is nearly equal to combined number of deaths from tuberculosis, malaria and HIV/AIDS. Medical graduates are supposed to be able to handle all types of emergencies, common or traumatic. Lack of ATLS, BCLS and ACLS certified doctors in emergency departments lead to improper and un-necessary delay in provision of medical care to patients.